For your eyes only [videorecording (Blu-Ray)] - Maibaum, Richard; Wilson, Michael G., 1942-; Moore, Roger, 1927-2017; Bouquet, Carole; Topol, 1935-2023; Johnson, Lynn-Holly; Glover, Julian, 1935-; Conti, Bill; Hume, Alan, 1924-2010; Easton, Sheena (Distributed by 20th Century Fox Home Entertainment, 2008)
A British spy trawler is accidentally sunk off the coast of a Warsaw pact county. On board the ship is a hi-tech encryption device called ATAC, which the British use to send launch instructions to their Polaris fleet. 007 James Bond's investigations leads to Greece where he meets Melina Havelock. She is out for revenge for the murder of her parents at the hands of the "Contact." James also meets Aristotle Kristatos and Milos Colombo. Evidence suggests that one of them is the Russian's 'Contact.' Both accuses the other. Melina and James set out to recover the ATAC device. Now, the two have to go up against the 'Contact.'